2020
DOI: 10.22271/j.ento.2020.v8.i2y.6637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different rice genotype against yellow stem borer (Scirpophaga incertulas Walker)

Abstract: The experiment was conducted in the consecutive two years 2016 and 2017 in the field conditions. As such, based on the overall mean values of two years' of investigations, the least percentage of dead-heart (1.87%) was recorded in case of Suraksha, followed by Kavya (4.50%), Lalat (5.59%), CR Dhan -303 (5.94%), CR Dhan -205 (6.77%), Sahbhagi Dhan (6.88%), CR Dhan -304 (7.02%) and Naveen (7.27%). These rice cultures were rated as promising and resistant against dead heart incidence, caused by YSB. The susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The mean data of all observations regarding the efficacy of different treatments against yellow stem borer revealed that, Chlorantraniliprole 0.4% G (4.24%), the most effective among all, were similar with the findings of Omprakash et al, [5], Rani et al, [7]. Followed by Spinosad 45% SC (4.54%), which lined with the findings of Chatterjee and Mondal [8], Madhu et al, [9], Acephate 75% SP (4.94%), similar results were supported by Sharanappa et al, [1], Kumari et al, [11].…”
Section: Resultssupporting
confidence: 86%
“…The mean data of all observations regarding the efficacy of different treatments against yellow stem borer revealed that, Chlorantraniliprole 0.4% G (4.24%), the most effective among all, were similar with the findings of Omprakash et al, [5], Rani et al, [7]. Followed by Spinosad 45% SC (4.54%), which lined with the findings of Chatterjee and Mondal [8], Madhu et al, [9], Acephate 75% SP (4.94%), similar results were supported by Sharanappa et al, [1], Kumari et al, [11].…”
Section: Resultssupporting
confidence: 86%
“…The present findings are in close conformity with Punithavalli et al, (2013) who reported that the contents of biochemicals such as phenol, orthodihydroxy phenol and tannins were negatively correlated with leaf folder damage indicating that these are defensive compounds contributing towards the rice yellow stem borer resistance. Further, Elanchezhyan et al, (2017) reported that higher concentration of total phenols observed in the resistance group could be one of the factors contributing towards tolerance with antibiotic effect against yellow stem borer.…”
Section: Resultsmentioning
confidence: 98%
“…Researches that was conducted for varietal engineering on rice, for example, involved so many research and actors, namely genome sequencing [3,4], breeding for water pressure [5], breeding for pests [6,7], pest evaluation [8,9], and related activity in varietal dissemination and development that were done by several institutions. With such a pattern, agricultural research follows a pyramid pattern, from basic, intermediate, and applied research activities or commercialization.…”
Section: Challenge Of Agriculture Research In Developing Countrymentioning
confidence: 99%